Pengaruh Ukuran Perusahaan, Kebijakan Dividen, Leverage, dan Profitabilitas terhadap Nilai Perusahaan - Nur Anisa; Sri Hermuningsih; Alfiatul Maulida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to examine the effect of firm size, leverage, dividend policy and profitability on firm value in the study of manufacturing companies in the food and beverages sector. This research uses quantitative research. The technique used in sampling is the purposive sampling method, namely the selection of samples is carried out with predetermined criteria. So that as many as 35 data were obtained from 7 food and beverages companies listed on the IDX during the 2016-2020 period. The data analysis method used is multiple linear regression analysis using the SPSS version 23 program. Based on the results of the study, it shows that: (1) firm size has no effect on firm value, (2) leverage has a negative and significant effect on firm value, (3) dividend policy has no effect on firm value, (4) profitability has a positive and significant effect on firm value. Keywords: firm size, leverage, dividend policy and profitability.